To Evaluate Povidone-iodine Effect On Post Appendectomy Surgical Site Infection - Rizwanullah Junaid Bhanbhroq; Khalil Ahmed Almani; Sadia Kazi; Navaid Kazi; Sumayya Kazi (Journal of Bahria University Medical and Dental College, 2021)
Objective: Evaluating the effects of Povidone- Iodine against the surgical site infection in post- appendectomy wound infection. Study design: Randomized clinical trial Place and duration: Department of Surgery, Isra University Hospital Hyderabad from January 2016 to December 2017. Subjects and Methods: Patients of acute appendicitis with classical clinical presentation were selected according to inclusion and exclusion criteria. 60 patients were those in which wound was irrigated with 1% povidone-iodine solution versus 60 patients in whom wound not irrigated with it before skin closure. Data was analyzed on SPSS 22.0 using Student t-test and Chi- square test respectively. Data was analyzed at 95% confidence interval (P=0.05). P-value of =0.05 was taken statistically. Results: Mean ± SD age of control and cases was noted as 22.5 ± 7.5 and 23.5 ± 6.5 years respectively (P=0.86). Male and female population in control and cases were noted as 45 (75%) and 15 (25%) & 47 (78.33%) and 13 (21.66%) respectively (P >0.05). Grade 4 pus discharging wound infection was noted in 3.33% in control compared to 1.66% in cases (P= 0.87). Normal wound healing (grad 0) was noted in 37 (61.6%) and 43 (71.6%) of control and cases respectively. In control grade 1-4 lesions were noted in 38.4% compared to 28.4% in cases (P < 0.05).